Analyzing Switch Regions of Human Rab10 by Molecular Dynamics Simulations - Alves, Levy Bueno; Castillo-Ordoñes, William O.; Giuliatti, Silvana (Anais do Simpósio Brasileiro de Bioinformática (BSB); 2020: Anais do XIII Simpósio Brasileiro de Bioinformática, 2020)
Rab10 is a small GTPase that regulates cellular processes by alternating between its GDP-bound inactive and the GTP-bound active states. Studies have shown that functional deficiencies in the Rab10 pathways are implicated in ciliophaties, gliobastomas and neurodegenerative diseases. Thus, the modulation of Rab10 activity may represent an interesting strategy in drug discovery. In order to identify potential Rab10 inhibitors for the treatment of Alzheimer’s disease, we studied the mobility of the switch1-interswitch-switch2 surface to understand the active “ON” and inactive “OFF” states of this enzyme. Even today, no in silico study on Rab10 linked to GTP and GDP has been carried out. We used molecular dynamics simulations to investigate the atomic movements of the Rab10 switch regions associated with these nucleotides. We found noticeable differences in the local ﬂexibility of switch 1 when Rab10 was linked to GDP. However, the heuristic method used was not able to successfully differentiate the ﬂexibility of switch 2 region. We hypothesized that the ﬂexibility of the switch 1 region can be used as an indicator of in silico studies that search potential competitive inhibitors based on nucleotides against Rab10. Furthermore, the present study can be useful for research that involves the description on-to-off process of other target proteins.